Socio-economic determinants & Dynamics of Debt Bondage: A descriptive Analysis of Brick Kiln Workers in Punjab Pakistan - Khan, Kashif Kamran; Shezadi, Amber (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
Debt bondage is the most prevalent form of forced labour worldwide. Brick kilns is a hotspot for this kind of slavery. It usually looks like an employment agreement but a violation of human rights lack of proper nutrition and extreme poverty has been eminent in these scenarios. The current study identifies the causes & effects of debt Bondage of Brick kiln workers in Punjab, Pakistan. This study investigates diverse aspects around the problem of debt bondage at brick kilns in the vicinity of Upper & South Punjab, Pakistan. A sample size of 150 respondents was interviewed from 35 brick kilns of three districts under simple random sampling. The study mainly focused on Health, Education & Economic issues & the causes and effects of bonded labor. It was observed that most young people due to the poor economic condition are forced to work in these brick kilns. The majority of workers around 84% gets daily wages between 600-900 per 1000 bricks which is very less according to the labor department that has fixed the minimum wage at Rs1110 per 1,000 bricks & most terrible thing is that out of giving amount they deduct Rs 100-200 or more deduct against their loan amount. Results conclude that working at brick kilns is very laborious, risky to health conditions, and working periods extending more than worldwide distinct limit has harmful effects. Major causes comprised lack of education, conflicts and lack of livelihood options. The of debt bondage were: lack of social contacts, hampered mobility, limited social status, poor economic status, limited access to health services, and bitter socialization and education of children. It is recommended that the national government must take tangible steps in the implementation of 1992 Act, regarding the elimination of bonded labor system, in ensuring to stop this inhumane practice.